A Systematic Review on Prosodic Entrainment in Spoken Dialogue - Raneen Waleed Khalid (Academia Open, 2025)
Background : Prosodic entrainment is a phenomenon in which many different fields intersect such as psycholinguistics, phonetics, and other fields. Aims: This systematic review tries to provide a comprehensive overview of existing research on prosodic entrainment in dialogues. Methods: Various studies are reviewed and compared to reach how speakers use their tone of voice to match it with other conversers. Different articles are reviewed to check their relativity to prosodic entrainment and the factor that affect entrainment. Results: It is shown that prosodic entrainment is affected by context, emotional state, task together with other factors. Discussion: Several studies on prosodic entrainment shed the light on the understanding of how people communicate. . Conclusions: The findings arrived at are supposed to contribute the dynamics of prosodic entrainment and its role in communication. Highlights: Highlights how tone and rhythm align in spoken interactions. Identifies emotional and contextual factors influencing entrainment. Bridges linguistic theory with communication practice. Keywords: Prosodic Entrainment, Spoken Dialogue, Communication, Psycholinguistics, Acoustic Matching